The effect of policies regulating tobacco consumption on smoking initiation and cessation in Spain: is it equal across socioeconomic groups? - Jaime Pinilla; Ignacio Abásolo (Tobacco Induced Diseases, 2017)
Introduction In Spain, the Law 28/2005, which came into effect on January 2006, was a turning point in smoking regulation and prevention, serving as a guarantee for the progress of future strategies in the direction marked by international organizations. It is expected that this regulatory policy should benefit relatively more to lower socioeconomic groups, thus contributing to a reduction in socioeconomic health inequalities. This research analyzes the effect of tobacco regulation in Spain, under Law 28/2005, on the initiation and cessation of tobacco consumption, and whether this effect has been unequal across distinct socioeconomic levels.